Editors-in-chief perceptions of patients as (co) authors on publications and the acceptability of ICMJE authorship criteria: a cross-sectional survey - Cobey, Kelly D.; Monfaredi, Zarah; Poole, Evelyn; Proulx, Laurie; Fergusson, Dean; Moher, David (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Access to, and awareness of, appropriate authorship criteria is an important right for patient partners. Our objective was to measure medical journal Editors-in-Chief’ perceptions of including patients as (co-)authors on research publications and to measure their views on the application of the ICMJE (International Committee of Medical Journals Editors) authorship criteria to patient partners. Methods We conducted a cross-sectional survey co-developed with a patient partner. Editors-in-Chief of English-language medical journals were identified via a random sample of journals obtained from the Scopus source list. The key outcome measures were whether Editors-in-Chief believed: 1) patient partners should be (co-)authors and; 2) whether they felt the ICMJE criteria for authorship required modification for use with patient partners. We also measured Editors-in-Chief description of how their journal’s operations incorporate patient partner perspectives. Results One hundred twelve Editors-in-Chief responded to our survey (18.7% response rate; 66.69% male). Participants were able to skip any questions they did not want to answer, so there is missing data for some items. 69.2% (N = 74) of Editors-in-Chief indicated it was acceptable for patient partners to be authors or co-authors on published biomedical research articles, with the remaining 30.8% (N = 33) indicating this would not be appropriate. When asked specifically about the ICMJE authorship criteria, and whether this should be revised to be more inclusive of patient partners, 35.8% (N = 39) indicated it should be revised, 35.8% (N = 39) indicated it should not be revised, and 28.4% (N = 31) were unsure about a revision. 74.1% (N = 80) of Editors-in-Chief did not think patients should be required to have an academic affiliation to published while 16.7% (N = 18) and 9.3% (N = 10) indicated they should or were unsure. 3.6% (N = 4) of Editors-in-Chief indicated their journal had a policy that specifies how patients or patient partners should be considered as authors. Conclusions Our findings highlight gaps that may act as barriers to patient partner participation in research. A key implication is the need for education and for consensus building within the biomedical community to establish processes that will facilitate equitable patient partners inclusion.

Plain English summary In academia, authorship on a research publication is a central means to obtain credit for one’s contribution to a research project. In order to guide authorship decision making and facilitate transparent processes, the International Committee of Medical Journal Editors (ICMJE) has produced recommendations for authorship. These recommendations are widely adopted by hundreds of medical journals. However, there is no research on whether the ICJME’s recommendations for authorship appropriately recognize the distinct contributions of patient partners to research. This survey study asked Editors-in-Chief about their perceptions of patient partners as authors and on the suitability of the ICMJE authorship criteria. We find that a 30.8%of medical journal Editors-in-chief do not view the inclusion of patient partners as authors on manuscripts as appropriate. Editors-in-chief reported wide ranging views on whether the ICMJE criteria for authorship were appropriate for patient partners. The implication of this work is that there is a need for education and for consensus building within the biomedical community to establish processes that will facilitate patient partners equitable inclusion in research, including on research outputs like publications.